Comparison of Plasma Dynamics in Coronal Holes and Quiet Sun Using Flux Emergence Simulations - Vishal Upendran; Durgesh Tripathi; Bhargav Vaidya; Mark C. M. Cheung; Takaaki Yokoyama (The Astrophysical Journal)
This paper presents a comparison of plasma dynamics in coronal holes (CHs) and quiet Sun (QS) through 2.5D MHD flux emergence simulations. The magnetic reconnection between the emerging and the preexisting flux leads to the formation of cool, dense plasmoids with hot boundaries, and hot and cool jets with velocities ≈50 km s ^−1 . We perform a spectral synthesis in spectral lines probing transition region and coronal temperatures. CHs show reduced intensities, excess upflows (downflows), and widths during the jetting (downflow) period when compared to QS. During the jetting and downflow periods, the velocity and line width of the hot spectral lines in CHs show a strong positive correlation with the vertical magnetic field at z = 0, while the intensity of the cooler lines shows a weak correlation, which is not seen in QS. During the jetting period in CH, we find upflows in Si iv to be correlated (anticorrelated) with upflows (downflows) in other lines, and downflows in CH in Si iv to be correlated (anticorrelated) with upflows (downflows) in other lines when compared to QS. During the downflow, we find no strong correlation between Si iv and other line velocities. The correlation during the jetting period occurs due to coincident, cospatial origins of the hot and cool jet, while the lack of correlation during the downflow phase suggests a decoupling of hot and cool plasma. These results demonstrate that flux emergence and reconnection with preexisting flux in the atmosphere support a unified scenario for solar wind formation and coronal heating.